Pediatric Wound Closure by a Tension-Relief System - Yaacobi, Dafna Shilo; Topaz, Moris; Kalish, Eyal; Hayun, Yehiel; Gurevich, Michael; Ad-El, Dean; Grush, Andrew E.; Olshinka, Asaf (Seminars in Plastic Surgery, 2022)
Surgical reconstruction in pediatric patients can often be complex. Primary wound closure is almost always the preferred technique in the reconstructive ladder; however, it is not always possible in pediatric patients. We report the pediatric use of the TopClosure Tension-Relief System, an innovative skin-stretching technique for secure primary wound closure of large defects. We modified the technique by fixating it to a protective dressing instead of the patient's skin, thus avoiding both staple scars and pain. A retrospective review of 112 patients aged 7 days to 18 years who underwent Tension-Relief System-assisted surgery at a tertiary medical center from 2010 to 2020 was conducted. Cases included congenital deformities, traumatic wounds, burn scars, and complicated-wounds, with or without hardware or deep tissue exposure. The use of the system avoided the need for multiple surgical sessions and for local or regional flaps. The technique was simple to use, with few complications, and led to satisfactory aesthetic and functional outcomes. The findings support using the technique in children and adolescents with challenging tension wounds. Herein, we report on our experience with the Tension-Relief System and detail four cases in which early or immediate closure was successfully achieved.
Keywords: Tension-Relief System; pediatric tension wound; TopClosure for pediatric use; challenging pediatric wounds